The Aplikasi Model Text Area Based Image Selective Encryption Menggunakan YoloV3, Arnold's Catmap dan AES Pada Pengamanan Konten Teks Pada Citra Digital - Riza, Ferdy; Azhari, Mulkan; Zulherry, Andi (Universitas Budi Darma, 2025)
sensitive content in digital images. This research proposes a selective encryption model based on text area detection in digital images, integrating object detection using You Only Look Once version 3 (YOLOv3), Arnold's Cat Map transformation, and the Advanced Encryption Standard (AES) algorithm. The model automatically identifies and selects areas containing text in the image using YOLOv3, applies Arnold's Cat Map for spatial disorganization, and then encrypts the transformed result with AES to ensure data security. System performance is evaluated through visual quality analysis using PSNR (Peak Signal-to-Noise Ratio) and SSIM (Structural Similarity Index) parameters, as well as encryption and decryption processing time. The test results show that this approach can maintain the integrity of non-text areas while providing strong protection for sensitive text areas without compromising efficiency or overall visual quality. This model has the potential to be applied in the context of securing digital documents, visual identities, and other sensitive data in images.